INTEGRASI STRATEGI PENDIDIKAN DAN KESEHATAN DALAM PENGUATAN FONDASI EKONOMI - Kamila Delfia Mulyadi (Educatus, 2023)
Education and health are two key pillars in human resource development that play a crucial role in supporting long-term economic growth. This study aims to examine how the integration of education and health strategies can strengthen the economic foundation of a nation. This research employs a qualitative approach using literature review as the primary method to analyze various policies, programs, and best practices in several developing countries. The findings indicate that the synergy between improving the quality of education and equitable access to health services significantly enhances workforce productivity, broadens economic participation, and accelerates social mobility. Furthermore, integrated policies in these two sectors contribute to more inclusive and sustainable development. The implications of this study highlight the importance of formulating holistic and cross-sectoral public policies, where education and health are not treated as separate entities, but as a unified strategic component in efforts to strengthen national economic competitiveness and resilience.